Introduction to Theological Libraries - Ćurić, Matina (The Theological Librarian's Handbook, 2020)
The Theological Librarian's Handbook is a multi-volume guide to the practice of theological librarianship intended for library staff who do not possess professional training in the field of library and information science. It offers perspectives and advice from leading experts in the field and best practices from theological libraries all over the world. Volume one of the series, Introduction Theological Libraries, introduces the reader to the world of theological librarianship and answers the basic questions: What are theological libraries, their purpose, types, and the role in the community in which they operate? Who are theological librarians and what are their possible career paths? What are theological libraries like across the globe? How are they organized and how do they serve humanity?